A quantitative comparison of tools for monitoring the abundance of crown-of-thorns starfish and coral cover - Emma Lawrence; Scott D. Foster; Samuel A. Matthews; David Williamson; Morgan S. Pratchett; Jason Doyle; Scott Bainbridge; Sven Uthicke; Peter C. Doll; Brano Kusy; Mohammad A. Armin; Mary C. Bonin (Coral Reefs, 2026)
Effective monitoring of crown-of-thorns starfish (COTS) populations and coral cover is critical for informing management of COTS outbreaks throughout their tropical Indo-Pacific range, including Australia’s Great Barrier Reef. However, existing monitoring tools such as manta tow and cull diver surveys have well-known limitations including accuracy and resource demands. This study evaluates a range of monitoring tools for assessing both COTS and coral populations. Tools that measure both COTS and coral include manta tow surveys, scooter-assisted large area diver-based (SALAD) surveys and surveys undertaken using the ReefScan towed camera platform. For COTS-only monitoring, we examine cull diver surveys and environmental DNA (eDNA) sampling. Data from side-by-side deployments on seven to ten reefs (depending on the tool) with varying COTS densities and coral cover were collected and analysed to calibrate estimates between tools. The calibration models developed will aid in integrating data from diverse sources and facilitate the translation of estimates based on one monitoring tool to another. Critically, the models provide a means of estimating COTS density (COTS per hectare) for monitoring tools that do not directly collect this measure, allowing more meaningful decision-making around ecological thresholds and enabling threshold-based management regardless of which tool collected the data. The study emphasises that each tool has specific applications for addressing knowledge gaps and informing management decisions, advocating for an integrated, multi-tool monitoring strategy that leverages the strengths of each tool to improve the overall effectiveness and efficiency of COTS and coral monitoring.

Phenological shifts and increases in voltinism within a moth community over a century of anthropogenic change - Emma M. Foster; Jason J. Dombroskie; Christopher A. Halsch; Thomas H. Q. Powell; Eliza M. Grames (Ecology, 2026)
In temperate ecosystems, warming temperatures can advance spring phenology, extend autumn phenology, disrupt dormancy regulation, result in phenological mismatch across taxa, and even lead to increases in the number of generations per year (i.e., increases in voltinism). Much of what we know about the impacts of global change on species phenology and voltinism comes from recent decades; however, anthropogenic warming began centuries ago. Using light trap datasets from 1889–1892 and 1919–1922, alongside contemporary records, we document long‐term changes in phenology and voltinism for 78 moth species, and changes in occurrence for 169 species, in New York, USA. From 1919–1922 to 2019–2024, we found an advance in spring phenology by 0.55 days per decade and an extension of the end of the flight period by 1.18 days per decade. This shift was largely driven by bi‐ and multivoltine species, which have added generations extending the end of their flight period by 1.58 days per decade compared to an extension of only 0.49 days per decade for univoltine species. We also document the apparent disappearance of 13 species from the region from 1889 to present, whose ranges now tend to be farther north and at higher elevations, possibly due to global change. As this region becomes warmer and wetter with ongoing climate change, more species may extend their active period or add more generations per year, with the potential for rapid adaptation and consequences for ecosystem function as some insect herbivores become more abundant.

Development of new global lake brGDGT-temperature calibrations: advances, applications, challenges, and recommendations - Emma J. Pearson; Steve Juggins; Harry Allbrook; Louise C. Foster; Dominic A. Hodgson; B. David A. Naafs; Tony Phillips; Stephen J. Roberts (Quaternary Science Reviews, 2025)

Speech Treatment for People with Cerebellar Multiple System Atrophy (MSA-C): A Pilot Randomised Controlled Trial of Two Approaches - Anja Lowit; Kaiyue Xing; D. Priya Shanmugarajah; Emma Foster; Suzanna Duty; David Young; Jan Stanier; Christopher Kobylecki; Marios Hadjivassiliou (The Cerebellum, 2025)
Speech problems are an early feature of Multiple System Atrophy (MSA). They can lead to social withdrawal and have significant impact on people’s quality of life. There is a considerable lack of clinical trials and clinicians lack guidance on how best to support this population. This project aimed to establish the feasibility and acceptability of a novel treatment approach, ClearSpeechTogether, in patients with the cerebellar variant of MSA (MSA-C), and to pilot an RCT comparing this treatment to standard speech and language therapy (SLT) treatment (ST). We recruited 24 patients with clinically probable MSA-C and dysarthria who were randomised to either treatment arm. Full data were available for 9 participants for ST, and 11 for ClearSpeechTogether. Both interventions lasted 6 weeks, ST offered 1 h of individual therapy a week, ClearSpeechTogether provided four individual therapy sessions over two weeks, followed by four weeks of daily, patient led group practice. Assessment and intervention were provided online via videoconferencing software. Data collection focused on feasibility, acceptability and signal of efficacy. Recruitment, conversion and attrition rates were within or close to target, and neither participants nor clinicians highlighted any acceptability issues. Communication outcomes were mixed, with biggest gains made in communication confidence and participation across both groups. Rapid decline in overall health status appeared to have impacted results. Results were generally positive and support the implementation of larger follow up trials. The study also demonstrated that people with MSA-C can benefit from speech therapy even at more severe stages of their disease progression.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

International Consortium to Classify Ageing-related Pathologies (ICCARP) senescence definitions: achieving international consensus - Emma Short; Robert T. R. Huckstepp; Kambiz Alavian; Winfried M. K. Amoaku; Thomas M. Barber; Edwin J. R. van Beek; Emyr Benbow; Sunil Bhandari; Phillip Bloom; Carlo Cota; Paul Chazot; Gary Christopher; et al. (GeroScience, 2025)

Urban wall lizards are resilient to high levels of blood lead - Maya M. Moore; Emma G. Foster; Ali Amer; Logan Fraire; Alyssa Head; Annelise Blanchette; Shala J. Hankison; Alex R. Gunderson; Eric J. Gangloff (Environmental Research, 2025)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Type 1 cryoglobulinemic neuropathy associated with lymphoplasmacytic lymphoma - Yew Li Dang; Emma Foster; Moira Finlay; Andrew Evans (Acta Neurologica Belgica, 2021)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Designing Monitoring Programs for Marine Protected Areas Within an Evidence Based Decision Making Paradigm - Keith R. Hayes; Geoffrey R. Hosack; Emma Lawrence; Paul Hedge; Neville S. Barrett; Rachel Przeslawski; M. Julian Caley; Scott D. Foster (Frontiers in Marine Science, 2019)

Ecology of a versatile canid in the Neotropics: gray foxes (Urocyon cinereoargenteus) in Belize, Central America - Bart J. Harmsen; Emma Sanchez; Omar A. Figueroa; Said M. Gutierrez; C. Patrick Doncaster; Rebecca J. Foster (Mammal Research, 2019)

Environmental engagement in troubled times: a manifesto - James D. Proctor; Jennifer Bernstein; Philip Brick; Emma Brush; Susan Caplow; Kenneth Foster (Journal of Environmental Studies and Sciences, 2018)

Erratum to: Widespread prevalence of cryptic Symbiodinium D in the key Caribbean reef builder, Orbicella annularis - Emma V. Kennedy; Nicola L. Foster; Peter J. Mumby; Jamie R. Stevens (Coral Reefs, 2015)

Widespread prevalence of cryptic Symbiodinium D in the key Caribbean reef builder, Orbicella annularis - Emma V. Kennedy; Nicola L. Foster; Peter J. Mumby; Jamie R. Stevens (Coral Reefs, 2015)

The trophodynamics of Southern Ocean Electrona (Myctophidae) in the Scotia Sea - Ryan A. Saunders; Martin A. Collins; Emma Foster; Rachel Shreeve; Gabriele Stowasser; Peter Ward; Geraint A. Tarling (Polar Biology, 2014)